2022
DOI: 10.1177/10812865221083046
|View full text |Cite
|
Sign up to set email alerts
|

An asymptotic modeling and resolution framework for morphology evolutions of multiple-period post-buckling modes in bilayers

Abstract: A stiff thin film bonded to a compliant substrate initially buckles into wrinkles, following with some intricate advanced instability modes when the compression exceeds higher thresholds. Here, we present an asymptotic modeling and resolution framework to quantitatively predict and continuously trace secondary bifurcation transitions in the non-linear post-buckling region. An advantage of this framework, besides its applicability to finite-strain deformations, is its asymptotic consistency with the three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although the structure of alternating packets of large and small undulations has been observed in some experiments, ,, the mechanisms of formation and evolution of such pattern are still unknown. Recently, Xu’s group theoretically obtained similar alternating packet structures in the cases of large prestretch (∼1.8) and small film–substrate modulus ratio (45–200). , But these formation conditions are different from our experiment with comparatively small prestretch (1.3) and extremely large modulus ratio (above 10 4 ). Further theoretical and simulation research is needed to illuminate the mechanisms of spontaneous strain localization and heterogeneous patterns with oscillatory amplitude and wavelength in a real film–substrate system.…”
Section: Resultsmentioning
confidence: 99%
“…Although the structure of alternating packets of large and small undulations has been observed in some experiments, ,, the mechanisms of formation and evolution of such pattern are still unknown. Recently, Xu’s group theoretically obtained similar alternating packet structures in the cases of large prestretch (∼1.8) and small film–substrate modulus ratio (45–200). , But these formation conditions are different from our experiment with comparatively small prestretch (1.3) and extremely large modulus ratio (above 10 4 ). Further theoretical and simulation research is needed to illuminate the mechanisms of spontaneous strain localization and heterogeneous patterns with oscillatory amplitude and wavelength in a real film–substrate system.…”
Section: Resultsmentioning
confidence: 99%
“…Computational results revealed that the strain energies of period tripling and period quadrupling modes are comparable in the post-wrinkling regime, and this was suggested as a possible explanation for the coexistence of these two wrinkling modes in experiments. Xu et al developed latticed models [33] and an asymptotic modelling and resolution framework [34] to trace the post-wrinkling behaviour of bilayers with pre-strained substrate. A period-tripling mode is observed when the substrate is highly pre-compressed.…”
Section: (Iii) Substrate Pre-compressionmentioning
confidence: 99%
“…The power of this method can be seen in the recent paper by Wang et al [1] who illustrated that quite a few existing linear and nonlinear plate theories can be recovered by appropriate specialisations. The first five papers in this special issue [26] are all concerned with further extensions/applications/validations of this method. In particular, Wang et al [2], Fu et al [3], and Wang et al [4] study, respectively, the nonlinear deformation of a clamped hyperelastic plate, morphology evolutions of multiple-period post-buckling modes in bilayers, and shape-programming of thin hyperelastic plates through differential growth.…”
mentioning
confidence: 99%
“…The first five papers in this special issue [26] are all concerned with further extensions/applications/validations of this method. In particular, Wang et al [2], Fu et al [3], and Wang et al [4] study, respectively, the nonlinear deformation of a clamped hyperelastic plate, morphology evolutions of multiple-period post-buckling modes in bilayers, and shape-programming of thin hyperelastic plates through differential growth. The method has recently been employed to derive a consistent rod theory for a linear elastic anisotropic material with circular cross-section [7].…”
mentioning
confidence: 99%